Data Quality as a Strategic Lever for MIS Success: Empirical Evidence from Indonesia's Digital Transformation - Adnan, Andi Astinah (Indonesian Scientific Publication, 2024)
In the era of digital governance, the success of Management Information Systems (MIS) hinges on the quality of data they process and deliver. Despite widespread implementation across Indonesia, many MIS initiatives fall short due to poor data quality, limiting their ability to improve decision making and organizational performance. This study investigates the extent to which data quality influences MIS success in Indonesia, using the DeLone and McLean IS Success Model as a guiding framework. A cross-sectional survey was conducted among 250 MIS users from public and private organizations across Indonesia. Data were collected using validated Likert scale instruments to measure data quality, system use, user satisfaction, and net benefits. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed to analyze both measurement and structural models. Results reveal that data quality significantly predicts MIS success, with strong effects on system use (β = 0.58), user satisfaction (β = 0.34), and net benefits (β = 0.29). The strongest pathway was observed through the mediation of user satisfaction, indicating that improvements in data quality translate to better system engagement and higher organizational gains. Among the six measured attributes, accuracy, relevance, and consistency were the most influential. These findings reinforce the importance of institutionalizing data governance strategies such as standardized protocols, data literacy training, and role-specific accountability. Furthermore, the Indonesian context emphasizes the need for adaptive models that account for infrastructural, cultural, and political variability. Overall, data quality is a foundational determinant of MIS success, requiring technical systems, organizational commitment, capacity building, and cross-functional coordination. The study offers actionable insights for policymakers and IT leaders to promote MIS performance and public sector innovation